A new species of Megaselia Rondani (Diptera, Phoridae) with wing-spots from China - Wang, Jian-Feng; Liu, Guang-Chun (Zootaxa, 2016)
The genus Megaselia was established by Rondani in 1856 with the type species Megaselia crassineura Rondani (=Phora costalis Roser, 1840) (Borgmeier 1968). About 1600 species are recorded and distributed all over the world (Fang & Liu 2015). In the genus Megaselia, species with wing-spots are rare. Only six species are recorded with wing-spots worldwide: M. conglomerata (Malloch) from North America (Borgmeier 1964), M. dickoni Wakeford & Disney and M. shadeae Hartop & Brown from Central America (Wakeford & Disney 1994, Hartop & Brown 2014), M. maculifera Beyer from Africa (Beyer 1965), M. chorogi Naumov from Georgia (Naumov 1979), and M. trimacula Fang & Liu from China (Fang & Liu 2015).